MnO2-Catalyzed Oxidative Alkylation of Enamides with Ethers via C(sp3)–H/C(sp2)–H Cross-Dehydrogenative Coupling and Hydrolysis Sequence - Hu, Zhiyan; Tang, Yucai; Zhang, Shan; Li, Xiaoqing; Du, Xiaohua; Xu, Xiangsheng (Synlett, 2015)
A new MnO2-catalyzed oxidative alkylation of enamides with a C(sp3)–H bond adjacent to an oxygen atom is described. This method achieves a C(sp3)-H/C(sp2)-H cross-dehydrogenative coupling and hydrolysis, thus providing efficient and general access to a variety of β-oxo ketones.
Keywords: C(sp3)–H/C(sp2)–H cross-dehydrogenative coupling; ethers; enamides; β-oxo ketones; radicals